Status of Anxiety and Depression among Caregivers of Mentally Ill Patients in a Tertiary Hospital - Shrestha, Gita (Journal of Nursing Education of Nepal, 2024)
Introduction: The main source of support for mentally ill patients is family, and they take the role of caregivers. Caregivers of mentally ill patients are at great risk of developing anxiety and depression. The main objective of the study was to find out the status of anxiety and depression among caregivers of mentally ill patients in a tertiary hospital.Methods: A descriptive cross-sectional research design was adopted. A purposive sampling technique was used to select 263 caregivers of mentally ill patients at the psychiatric department of Tribhuvan University Teaching Hospital. Data was collected through an interview technique with a semi-structured questionnaire, along with a pretested and validated Nepali version of the General Anxiety Disorder and Patient Health Questionnaire scale to assess anxiety and depression, respectively. SPSS version 16 was used to analyze the data using descriptive and inferential statistics (chi-square tests). Ethical consideration was maintained throughout the study.Results: Anxiety and depression among caregivers of mentally ill patients were 19.8% and 18.2%, respectively. Risk factors significantly associated with anxiety and depression were sex and health problems of caregivers, social support received by caregivers, and sex of the patient. The type of mental illness of the patient was significantly associated with anxiety, while ethnicity and educational level were significantly associated with depression among caregivers.Conclusion: Minimal anxiety and mild depression were seen among caregivers of mentally ill patients. Thus, there is a need for a screening test and regular psychological counseling for the caregivers of mentally ill patients to prevent mental illness.
Keywords: Anxiety; caregiver; depression; mentally ill patients